Cognitive therapy across the lifespan - Reinecke, Mark A.; Clark, David A. 1954- (Cambridge University Press, 2004)
In this balanced and critical overview, an international team of experts examines systematically the evidence in support of the effectiveness of cognitive-behavioral approaches to treating clinical problems across the lifespan. They analyse the cognitive models of psychopathology on which these treatments are based, and identify the clinical and conceptual problems, giving specific recommendations for addressing them. The range of disorders covered includes depression, anxiety, panic disorder, schizophrenia, OCD, personality disorders, eating disorders, post-traumatic stress disorder, conduct problems and addiction